SEMIOTIC SEMANTICS AND LINGUO-COGNITIVE MODELS - Hakimov Muhammad Khojakhonovich (Modern American Journals, 2025)
This study examines the linguo-cognitive and pragmalinguistic mechanisms underlying implicit meaning, implicit thought, and implicit knowledge in communication. The research is grounded in cognitive linguistics and explores how linguistic and non-linguistic expressions reflect the structure of human cognition. Using examples from Uzbek literary discourse, the paper demonstrates how implicit meanings emerge in context through culturally, religiously, and socially conditioned cognitive frameworks. The analysis focuses on how latent knowledge interacts with lexical and nonverbal cues, revealing the deeper conceptual organization of meaning. The study contributes to the field of cognitive pragmatics by clarifying the hierarchical relationship among implicit knowledge, implicit meaning, and implicit thought, and by identifying their manifestation in communicative acts and literary language.
Keywords: Cognitive linguistics, implicit meaning, implicit thought, implicit knowledge, linguo-cognitive model, pragmalinguistics, literary discourse, communication, contextual meaning, conceptualization